2004
DOI: 10.1089/dna.2004.23.836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Human Anti-HIV-1 gp41 IgM Monoclonal Antibody Designated Clone 37

Abstract: Human monoclonal antibodies (HuMAbs) demonstrate great potential for passive immunotherapy against HIV-1. The gp41 transmembrane envelope glycoprotein of HIV has an important role in the pathogenicity of AIDS and importantly displays considerably less hypervariability than the gp120 surface envelope HIV glycoprotein, which makes it particularly a better candidate for the development of passive and active immunotherapies. The general aim of this study was to develop HuMAbs to HIV surface glycoproteins and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These results are consistent with our immunoprecipitation experiments that indicated that mAb 1E8a bound to hMC4R and rMC4R with high affinity, whereas the mAb 2G2 interacted only with the NT peptide The affinity of the mAb 1E8a and the mAb 2G2 for the NT peptide were in the same range (1.3 ϫ 10 Ϫ8 and 3.7 ϫ 10 Ϫ8 M, respectively). They are relatively high for an IgM isotype, but other high-affinity IgM mAbs have been described previously (Ballard et al, 1983;Suenaga and Abdou, 1992;Cao et al, 2004). The small difference between the affinity of mAbs 1E8a and 2G2 cannot explain why the latter did not interact with the MC4R.…”
Section: Discussionmentioning
confidence: 86%
“…These results are consistent with our immunoprecipitation experiments that indicated that mAb 1E8a bound to hMC4R and rMC4R with high affinity, whereas the mAb 2G2 interacted only with the NT peptide The affinity of the mAb 1E8a and the mAb 2G2 for the NT peptide were in the same range (1.3 ϫ 10 Ϫ8 and 3.7 ϫ 10 Ϫ8 M, respectively). They are relatively high for an IgM isotype, but other high-affinity IgM mAbs have been described previously (Ballard et al, 1983;Suenaga and Abdou, 1992;Cao et al, 2004). The small difference between the affinity of mAbs 1E8a and 2G2 cannot explain why the latter did not interact with the MC4R.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, we cannot rule out the possibility of the existence of a small proportion of anti-CBD1 antibodies that react with specific linear epitopes. Recently, a human IgM mAb C37 binding to the sequence IWNNM in the caveolin-binding motif was isolated from an HIV-seropositive long-term non-disease progressing patient (Cao et al 2004). Whether or not mAb C37 has the capacity to neutralize HIV-1 infection has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…al. (2004) [ 35 ], and we found that CL3 binds to peptide 2025. This antibody can successfully neutralize HIV-1 clade B clinical isolate (Figure 4 ).…”
Section: Resultsmentioning
confidence: 89%